Batman and the Sticky-fingered Maiden: Psychology as an Interpretive Practice - Kirsten Klingle (University of Calgary, 2015)
This paper is a short reflection on the nature of psychology as an interpretive practice by exploring the question: how, if at all, does interpretation apply to the field of psychology? This author presents the notion that interpretation is relational and that both client and therapist histories shape the individual’s ways of interpreting experience and prejudices that arise in therapeutic practice.